Edificio CAPSA-CAPEX (2003)
Edificio costero de oficinas en Vicente López, Buenos Aires.
Keywords: ARGENTINA; BUENOS AIRES; VICENTE LOPEZ; EDIFICIOS DE OFICINAS; EDIFICIOS COMERCIALES; BENADON, RICARDO; BERDICHEVSKY, CARLOS; CHERNY, RUBEN; ROBINSOHN, GUSTAVO; EDIFICIOS INTELIGENTES